Interfering Bodies Political Protesters in Philippine Streets - Arcilla, Chester C. (Philippine Social Sciences Review; Vol 62 No 1: January-June 2010, Ed. Eric Manalastas, 2011)
Dominant protest theories assume a homogenous rational actor pursuing political objectives and focus on the structural environment that surrounds protests, and neglect the protesting body.  I consider the body as an articulated articulate agent and study the bodies of protesters as they struggle for emancipatory politics on the street.  I look at how street protesters use their bodies as instruments of political propaganda by physically interfering in the street, and how this corporeal experience of marching shoulder to shoulder in turn strengthens their politics.  I analyze how the organization and formations of street protests preserve and strengthen the recalcitrant collectivity of protesting bodies.  I then focus on the line of bodily engagement, the composite team and study how its members use their bodies to assert their politics and minimize the physical risk as they defensively engage hostile bodies.   By focusing on the protesting body, the process of collective formation and the development of political consciousness that emanate from the continuous reflection of the shared corporeal protest experience and marginality are recognized.  This dialectical link between corporeal experience and political consciousness through the body allows for a political agency characterized by difference and dynamism unified by a shared experience.
Keywords: street protests, Phillippines